1997
DOI: 10.1097/00008483-199701000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Monitoring in Patients With Peripheral Arterial Occlusive Disease

Abstract: These findings indicate that an accelerometer and pedometer are two instruments that reliably estimate the physical activity levels of patients with PAOD over 2 consecutive days. Furthermore, the activity questionnaires, suggesting that activity monitoring measures a different component of activities in patients with PAOD with intermittent claudication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 19 publications
3
52
0
Order By: Relevance
“…Consequently, the average step count (6,752±2,659 steps/day) in this investigation was slightly higher than that reported from earlier evaluations of a chronic disease population. [12][13][14]23 These findings are not surprising given that our participants regularly attended the CRP and they were also likely to have a greater functional capacity than the subjects observed in the aforementioned studies. Although the average step count for the subjects in the presents study corresponded to the minimal goal for PAEE in secondary prevention (1,500 kcal/week) ( Table 2), 48% of patients failed achieve this minimal goal.…”
Section: Circulation Journal Vol72 February 2008mentioning
confidence: 63%
See 3 more Smart Citations
“…Consequently, the average step count (6,752±2,659 steps/day) in this investigation was slightly higher than that reported from earlier evaluations of a chronic disease population. [12][13][14]23 These findings are not surprising given that our participants regularly attended the CRP and they were also likely to have a greater functional capacity than the subjects observed in the aforementioned studies. Although the average step count for the subjects in the presents study corresponded to the minimal goal for PAEE in secondary prevention (1,500 kcal/week) ( Table 2), 48% of patients failed achieve this minimal goal.…”
Section: Circulation Journal Vol72 February 2008mentioning
confidence: 63%
“…10 The reported average daily step count for a group of peripheral arterial disease patients was nearly 4,500 steps/day 12 and it ranged from 3,500-4,300 steps/day in heart disease patients. 13,14,23 Hoodless et al demonstrated that chronic heart failure patients had a 60% reduction in step count compared with age-matched healthy controls.…”
Section: Circulation Journal Vol72 February 2008mentioning
confidence: 99%
See 2 more Smart Citations
“…[24] In one report, the physical activity values from the accelerometer correlated moderately with the Minnesota Leisure Time Physical Activity Questionnaire (r = 0.33; P < 0.01). [25] No significant associations were reported between the 6-minute walking test and an ambulatory activity monitor in older adults residing in continuing care retirement communities [26] or in patients with peripheral arterial disease (p >.05) [27] No significant associations were observed between the Physical Activity Scale for the Elderly (PASE) and an ambulatory activity monitor in older adults residing in continuing care retirement communities. [26] Similarly, ambulatory activity monitoring did not correlate significantly with self-reported functional status in patients with chronic obstructive pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%